Kemampuan Pemecahan Masalah dan Disposisi Matematis Siswa: Tinjauan pada Pembelajaran dengan Pendekatan Pendidikan Matematika Realistik (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Mathematics plays a crucial role in developing students' critical thinking skills and problem-solving abilities, especially in the face of evolving challenges in the global era. However, mathematics learning in Indonesia is often too focused on memorizing formulas and procedures that hinder students' cognitive development and disposition. This study aims to evaluate the effect of the application of the Realistic Mathematics Education approach on improving students' problem-solving skills and mathematical disposition in the Two-Variable Linear Equation System material. The method used was a pseudo-experiment with a posttest-only control group design. This study involved two classes of grade VIII students at SMP Negeri 6 Tondano, where one class was treated with the PMR approach as an experimental group, while the control group was taught using conventional methods. The data collected included the results of a description test to measure problem-solving skills and a mathematical disposition questionnaire to assess students' attitudes towards mathematics. Data analysis was carried out using a t-test. The results revealed that the average scores of problem-solving skills and mathematical dispositions of students taught with the PMR approach were significantly higher compared to the control group. This suggests that this approach based on real-world contexts can improve understanding of concepts, stimulate critical thinking, and form positive attitudes towards mathematics. The implications of this study show the importance of applying a contextual approach in mathematics education to improve the quality of learning as a whole. Therefore, teachers must be encouraged to implement learning strategies that connect abstract concepts with real life to make learning more meaningful and effective in the long run.